Generalization of sum representation functional equations-I - Pl. Kannappan; V. Sathyabhama (International Journal of Mathematics and Mathematical Sciences)
This paper contains the solution of a functional equation which is a generalization of a functional equation arising in a characterization of directed divergence and inaccuracy.